Sincronización de la onda folicular mediante el uso de buserelina en la llama (Lama glama) - Ferrer, M.S. (2002)
The objective of the study was to synchronize follicular wave emergency using busereline in a group of llamas that were at different stages of their follicular waves. We used 16 non-pregnant, nonlactating females divided according to their follicular dynamics determined ultrasonographically three days previously, into 4 groups: I: follicles smaller than 6 mm; II: growing follicles from 7 to 10 mm; III: maturing follicles from 8 to 14 mm and IV: regressing follicles, decreasing over two consecutive days. The animals received 8 µg of busereline (day 0) and ovarian activity was followed using ultrasound scanning until a dominant follicle ( ?7 mm) was detected. The smallest mean maximum follicular diameter was observed on day 3, there being no significant differences between the 4 groups (P=0.50).\nThe time interval from the GnRH injection to the detection of a follicle ?7 mm was 6.25 ± 1.29 days in group I; 5.5 ± 1.8 days in group II; 5.5 ± 1.1 days in group III and 8.66 ± 1.88 days in group IV. The moment of the detection of a dominant follicle was not statistically different (P=0.26). In conclusion, the use of busereline in llamas that are in different follicular phases synchronizes the emergence of the follicular wave and permits starting superstimulatory treatments between days 3 and 6 after its injection.